The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

A tutela jurídica do capital intelectual das sociedades empresárias - Abdallah, Ana Claudia Karam (Universidade de São Paulo, 2009)
Na atual era pós-industrial, o conhecimento passa a ser o principal fator de produção da economia. De fato, ele confere à empresa seu maior diferencial competitivo no mercado globalizado: a inovação, ou seja, a capacidade de, continuamente, gerar novos produtos, processos e serviços ou aperfeiçoar os existentes. A organização da empresa em sociedade empresária possibilita a criação de conhecimento coletivo oriundo do trabalho profissional dos seus sócios, administradores e empregados, fato que originou a expressão capital intelectual, cunhada no âmbito econômico para designar o patrimônio empresarial de natureza intangível resultante de contribuições intelectuais. Como o Direito é precedido da evolução das sociedades e da Economia, nota-se a importância de sempre se buscarem soluções jurídicas às novas realidades socioeconômicas que surgem ao longo da história. Diante disso, a análise da natureza jurídica e das formas de tutela do capital intelectual torna-se imperativa para a identificação e apropriação privada desse patrimônio pela sociedade empresária, seja por meio do exercício de direitos de exclusivo, seja pela implementação de mecanismos de governança capazes de assegurar a diferenciação da atividade empresarial no mercado e a necessária coibição de práticas de concorrência desleal. In the current post-industrial age, knowledge becomes the main production factor of the economy. Indeed, it provides the company with its main competitive advantage in the globalized market: the innovation, that is, the capacity of continuously generating new products, processes and services or enhance the existing ones. The companys organization as business company allows the creation of collective knowledge arising from the professional work of its partners, officers and employees, which fact originated the term intellectual capital, created in the economic scope to designate the corporate equity of intangible nature resulting from intellectual contributions. As the Law came after the evolution of the companies and of the Economics, it is noted the importance of the constant search for legal solutions, the new socioeconomic realities that appear along the history. In view of that, the analysis of the legal nature and of the forms of protection of the intellectual capital becomes critical for the identification and private appropriation of such equity by the business company, either by means of the exercising of exclusive rights or by the implementation of governance mechanisms capable of ensuring the differentiation of the corporate activity in the market and the required restraining of unfair competition practices.
Keywords: Capital social; Concorrência desleal; Direito empresarial; Estabelecimento comercial; Intangible; Intellectual capital; Intellectual property; Propriedade intelectual; Sociedade comercial; Unfair competition